The Effectiveness of a Realistic Mathematics Education to Increase Higher Order Thinking Skill (HOTS) of Secondary School Students - Muhammad Ammar Naufal; Ibrahim Abdullah Alshaye (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This study aims to determine the effectiveness of using a realistic mathematical approach to the Higher Order Thinking Skill (HOTS) of SMA Negeri 2 Majene (SMAN 2 Majene), Indonesia. The subjects of this research were four students of class XI at SMAN 2 Majene. This research used a descriptive qualitative method. The instrument used was PISA-based HOTS questions developed based on a realistic mathematical approach to test students' HOTS. The average score obtained by students in answering test questions ranged from 61-80. It was concluded that the HOTS of SMA Negeri 2 Majene students were good. It showed that the realistic mathematics education effectively increased students' HOTS.